(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was verify the eating habits of high school teenagers students of public schools from the town of São Gabriel da Cachoeira, Amazonas, regarding to the food’s consume. The sample, calculated based on records of SEDUC, was comprised for 334 individuals of both sexes, who answered the COMPAC II questionnaire of NuPAF-CDS-UFSC 2011. It was observed the component items of the scale eating habits through percentage, during 7 days of a week, overall and by sex. The eating habits of students from São Gabriel da Cachoeira were considered adequately balanced with daily frequency peaks 3-4 days. By sex, the higher proportions were for females, including soft drinks, candies and savoury, commendable for both sexes in a 7-day consume of beans, rice, milk and dairy products. The male could improve the consume of fruits and juices. The results suggest, in any way, an indication of nutritional education to give meaning to what is good and correct with consciousness what needs to be understood and developed eating habits at this stage of growth, which will make a difference in the course of decades forward, concerning to population health.